The biopsychosocial-spiritual health of active duty women - Lacks, Meghan (Mental health, religion & culture, 2018)
Women have been an active part of the military since the beginning of American history, holding various roles in the military for centuries. The purpose of this review is to explore the literature pertaining to the biopsychosocial and spiritual health of active duty women. These comparisons help to highlight factors that are most unique to women who are serving in our active duty armed forces. The current review revealed that while active duty women and men report similar levels of resiliency, and women may be no more susceptible to the negative effects of combat than men, there is evidence that active duty women experience higher levels of posttraumatic stress due to physical and sexual trauma in the military aside from combat exposure. Findings suggest that further research is needed to better understand the unique challenges of women in the military in order to create service delivery models that support the BPSS health of women in order to maintain mission readiness and retain women in the military.